In Vitro Activities of Florfenicol against Bovine and Porcine Respiratory Tract Pathogens - Priebe, Saskia (American Society for Microbiology, 2003)
Florfenicol in vitro activities for a total of 756 bacterial isolates from respiratory tract infections of cattle and swine were comparatively investigated by the agar diffusion method and the microdilution broth method. Florfenicol showed high in vitro activity against Pasteurella multocida, Mannheimia haemolytica, Actinobacillus pleuropneumoniae, and Streptococcus suis, with all of the isolates inhibited by ≤2 μg of florfenicol per ml.